Effect of Interval Time between Corrosive and Abrasive Challenges on a Nanoparticulate Composite Resin - Vilela, Ana Laura Rezende; Machado, Alexandre Coelho; Queiroz, Lucas Lemes; Batista, Pedro Henrique Mauro; Faria-e-Silva, André Luís; Menezes, Murilo de Sousa (European Journal of Dentistry, 2021)
Objective This study aimed to evaluate the effect of interval time after acidic beverage intake and brushing on roughness and hardness of resin composite.Materials and Methods Nanofilled resin composites were tested as per interval time (no interval, 15 or 30 minutes) between aging media (isotonic, sports drink) and brushing. Specimens (n = 9) were subjected to three cycles daily for 5 days with immersion in beverage followed by simulated brushing (585 strokes). The brushing (control) group was submitted only in brushing cycles. Roughness and microhardness were analyzed in the baseline and end of the experiment. Surface morphology was analyzed by using scanning electron microscopy (SEM).Statistical analysis Data were analyzed by one-way ANOVA and Tukey’s honestly significant difference (α = 0.05).Results Roughness was higher in no interval group and lower in 30 minutes and control. The 15 minutes present no statistical difference between control, 30 minutes and no interval. The hardness not present difference between groups. The SEM showed the no interval more roughness than 15 and 30 minutes, control and baseline.Conclusion The interval time between erosive and abrasive challenge is important to preserve the smoothness surface of composite resin.
Keywords: composite resins; toothbrushing; beverages